EFEITO DA ADIÃ‡ÃƒO DE POTÃSSIO SOBRE O PH DE ALGUNS SOLOS DO ESTADO DE SÃƒO PAULO - Mello, Francisco de A. F. de; Cardoso, Antonio; Athayde, Manoel L. F.; DemattÃª, Maria E. P.; Pitelli, Robinson A.; Arzolla, Sylvio (REVISTA DE AGRICULTURA, 2020)
EFEITO DA ADIÃ‡ÃƒO DE POTÃSSIO SOBRE O PH DE ALGUNS SOLOS DO ESTADO DE SÃƒO PAULO